2011
DOI: 10.1111/j.1600-9657.2011.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal root fracture treated with MTA, a case report with a 10-year follow-up

Abstract: Root fractures occur more frequently in fully erupted permanent teeth with closed apices in which the completely formed root is solidly supported in the bone and periodontium. The consequences can be complex because of combined damage to the pulp, dentine, cementum, bone, and periodontium. Management of horizontal root fractures and lateral luxation depends on several factors, with the result that various clinical modalities have been suggested. This case report describes the treatment and 10-year follow-up of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 22 publications
3
39
0
1
Order By: Relevance
“…Moreover, it induces the formation of cementumlike hard tissue when placed adjacent to periradicular tissues (14). MTA has been recommended for teeth with open apices (15); however, the use of MTA in intraalveolar root fractures has only been described in a few case reports (16)(17)(18)(19)(20). Some authors have stated that it is too early to make a comparison of MTA as an alternative to Ca(OH) 2 and GP in root fractures (21).…”
mentioning
confidence: 95%
“…Moreover, it induces the formation of cementumlike hard tissue when placed adjacent to periradicular tissues (14). MTA has been recommended for teeth with open apices (15); however, the use of MTA in intraalveolar root fractures has only been described in a few case reports (16)(17)(18)(19)(20). Some authors have stated that it is too early to make a comparison of MTA as an alternative to Ca(OH) 2 and GP in root fractures (21).…”
mentioning
confidence: 95%
“…Yildirin and Gencoglu observed that the area of the MTA and fracture line was fully surrounded with new hard tissue formation. Healing with the interposition of connective tissue was found in the 10-year follow-up radiographic although MTA was extruded between the fragment [26]. Kim et al initially identified 22 teeth in 21 patients who had horizontal intra-alveolar root fractures and who had received endodontic treatments with MTA, 17 teeth exhibited healing of the root fracture and 2 teeth showed interposition of granulation tissue [27].…”
Section: Discussionmentioning
confidence: 99%
“…120 The treatment outcome for fractured teeth may be influenced by several factors, such as the degree of dislocation, stage of root formation, location of the fracture, interval between trauma and treatment, and type of dental trauma (displacement of the coronal fragment compared with no displacement of the coronal fragment). 121 One problem is that the fracture line will only be detected if the X-ray beam passes directly through it. The absence of radiographic signs when the Xray beam is not parallel to the plane of the root fracture, tooth displacement and/or alveolar bone fracture is a limitation of intra-oral PRs.…”
Section: Assessment Of Dental Traumamentioning
confidence: 99%